Transient Equivalent Modelling of a Wind Farm Based on QPSO-Based Wind Turbine Fault Ride-Through Control - Jianan He; Shenbing Ma; Xu Zhang; Meiling Luo; Lei Li; Jian Niu; Haitao Liu; Ping Jin; Yabo Liang (Energies)
At present, the equivalent modeling method of wind farms mostly adopts single-machine multiplication equivalence, which has the deficiencies of large model error and difficulty in accurately reflecting the fault transient characteristics of wind farms, which imposes limitations on the security and stability analysis of the power system. For this reason, this paper proposes an equivalent modeling method that can accurately reflect the fault ride-through characteristics of wind farms. Based on the control mechanism of direct-drive wind turbines, this method first analyzes the fault ride-through operating characteristics of wind turbines and establishes a single-machine fault transient model; then, taking the fault ride-through control characteristics of wind turbines as the criteria for subgroups, it calculates the relevant parameters of the group through weighted aggregation and QPSO algorithm, and constructs the fault transient equivalent model of each group; finally, combining with the principle of loss conservation, it integrates and obtains the fault transient equivalent model of the whole wind power field. Finally, the equivalent fault transient model of the whole wind farm is obtained by combining the loss conservation principle. Simulation verification shows that the established equivalent model can accurately reflect the dynamic characteristics of the wind farm, and the maximum percentage error of voltage and active power is no more than 10% in comparison with the corresponding detailed model under the same kind of fault perturbation, which not only meets the requirements of China’s wind farm modeling standards, but also shows higher adaptability and accuracy under different working conditions compared with other equivalent modeling methods. Especially under the extreme three-phase zero-passage fault condition, the maximum error of voltage and active power does not exceed 2%, which provides a reliable basic tool for the safety and stability analysis of wind farms.